Assessment of Yield and Yield Attributes of Tossa Jute as Affected by Variety and Field Duration (Bangladesh Agronomy Journal, 2023)
A study was conducted at the Jute Research Sub-Station (JRSS), Tarabo, Narayanganj in 2022 to find out the suitable varieties and field duration for tossa jute (Corcorus olitorius) harvesting for better fibre and stick yield production. The treatment was assigned of tossa jute varieties (3) viz., BJRI Tossa pat-7, Robi-1 (BJRI Tossa pat-8) and Indian variety JRO-524 and four field durations viz. 90, 100, 110, and 120 days, respectively. A factorial RCBD design with three replications was used. Results showed that varieties and field duration significantly affected plant height, base diameter, fibre yield and stick yield. The var. JRO-524 had the highest fibre yield (2.30 tha−1) than BJRI Tossa Pat-7 and Robi-1(2.10 tha−1 and 2.25 tha−1 respectively) when harvested at 90 days after sowing (DAS). On the other hand, BJRI Tossa pat-7 and Robi-1 produced significantly higher fibre yields (3.20 tha−1 and 3.55 tha−1; 3.45 tha−1 and 3.80 tha−1 respectively) and stick yields (6.15 tha−1, and 6.25 tha−1; 6.67 tha−1, and 6.84 tha−1 respectively) at harvesting 110 and 120 DAS. The results showed that var.  BJRI Tossa pat-7 and BJRI Tossa pat-8 could be a better fibre yield and stick yield production when it could be harvested at 120 DAS.Bangladesh Agron. J. 2023, 26(1): 18-27